The Challenges of Islamic Religious Education in the Industrial Revolution 4.0 - Zubairi, Zubairi; Nurdin, Nurdin (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2022)
The purpose of this research is to find out the challenges of Islamic education in facing the era of the industrial revolution 4.0. The type of research used is library research. While the data obtained is a descriptive narrative about Islamic education. The results of the study show that there are three things that must be utilized by educators in the Revolution 4.0 era, including the Internet of things in the world of Education (IoT), Virtual/Augmented reality in the world of education, and the use of Artificial Intelligence (AI). Islamic religious education teachers are required to have high competence to produce students who are able to answer the challenges of the Industrial Revolution 4.0. So an Islamic religious education teacher must have principles in the learning process, including; Learning Process, Active, Innovative, Creative Effective, efficient and educative, and fun (PAIKEM) and the ability to integrate technology into learning.